Manajemen Sarana dan Prasarana di SD Kartika Wirabuana 07 Manado - Martinus M. Krowin (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to analyze and describe the management of facilities and infrastructure at Kartika Wirabuana Tujuh Elementary School Manado. This research is motivated by the existence of a gap in facilities and infrastructure that still occurs in schools, meanwhile schools are required to improve facilities and infrastructure in order to support the smooth teaching and learning process which in turn will improve the quality of education in schools in particular and the world of education in general. Therefore, schools are required to be able to manage facilities and infrastructure in accordance with the principles of education management so that educational goals can be achieved effectively and efficiently. This study uses a qualitative descriptive approach that aims to find out how the process of management of facilities and infrastructure at Kartika Wirabuana Tujuh Elementary School Manado. Management of facilities and infrastructure at Kartika Wirabuana Tujuh Elementary School Manado starts from planning, procurement process, inventory process, use of facilities and infrastructure, maintenance, control activities and activities for the elimination of facilities and infrastructure. The planning process for facilities and infrastructure begins with conducting a needs assessment and continues with holding a teacher council meeting to determine the facilities and infrastructure that need to be procured. The results of the meeting are proposed to the Foundation for realization. The procurement process is based on the consideration of the Foundation. After the procurement process is continued with an inventory of facilities and infrastructure in order to easily check their existence and use. The use of facilities and infrastructure follows the procedures set by the school. In order for facilities and infrastructure to be used properly, it is necessary to make efforts to maintain and maintain them so that they are safe and can be used properly. The planning process up to the use of facilities and infrastructure in order to run well, it is necessary to have supervision carried out by school leaders and foundations